Correlation of ADC Map with the Ki-67 Index in Glial Tumor Prognosis in Patients of Stereotaxic Ward - Shahmohammadi, Mohammadreza; Fazeli, Mohamad Ali; Janamiri, Zahra; Asgari Gorji, Reza (International Clinical Neuroscience Journal, 2017)
Background and Purpose: There has been no report in which preoperative evaluation of ADC for prediction of post therapeutic outcome was presented. The aim of our study was to retrospectively evaluation the use of the apparent diffusion coefficient (ADC) for the prediction of malignancy and the outcome of malignant astrocytic tumors. Methods: We reviewed MRI of 26 male and 14 female patients with a pathologic diagnosis of a malignant astrocytic tumor. Results: There was a relatively significant correlation between Ki-67 LI and minimum ADC was noted for the asterocitoma group (r=−0.701, P<0.001) or the oligodendroglioma group (r=−0.634, P =0.027) and more significantly in oligoastrocitoma group (r=−1.000) separately. There was a significant negative correlation between these parameters for the malignant glial and oligodenroglial tumors as a whole (r=−0.634, P =0.027). Conclusion: The ADC analysis could be considered as one of the clinically accessible techniques used for prediction of outcome of malignant astrocytic tumors, and it might be useful for planning primary treatment modality in patients with these malignant tumors.